Intensive Transactional Analysis Psychotherapy (ITAP): A Single-Case Time Series Study - Messina, Irene; Scottà, Francesco; Benelli, Enrico; Bianco, Francesca; Sambin, Marco (Journal of Psychology and Psychotherapy Research, 2018)
Intensive Transactional Analysis Psychotherapy (ITAP) integrates Transactional Analysis and brief psychodynamic approaches for the intensification of therapist intervention based on the moment-by-moment analysis of intrapsychic and interpersonal process of the patient. We present a quantitative and qualitative, time series study to evaluate ITAP therapy effectiveness in a single case. Quantitative outcome data were collected using the Clinical Outcome in Routine Evaluation – Outcome Measure, in 3 baseline measures, after each session and in 3 follow-up evaluations. Qualitative data were collected using the Change Interview that allows the documentation of more relevant changes for the patients and a scoring of their relevance. Quantitative results provide evidence of ITAP effectiveness, with very large ES of self-reported change. Qualitative results are consistent with the recovery observed in self-reported measures and confirm that the perception of the patient is consistent in several points with ITAP theory.